2015
DOI: 10.1039/c3nr04421a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized iron oxide nanoparticles for controlling the movement of immune cells

Abstract: Immunotherapy is currently being investigated for the treatment of many diseases, including cancer. The ability to control the location of immune cells during or following activation would represent a powerful new technique for this field. Targeted magnetic delivery is emerging as a technique for controlling cell movement and localization. Here we show that this technique can be extended to microglia, the primary phagocytic immune cells in the central nervous system. The magnetized microglia were generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…(Reichel, Tripathi, & Perez, 2019;Zanganeh et al, 2016). Finally, in preliminary studies, others have also attempted to drive immune cells (microglia) toward regions of interest by functionalizing them with magnetic nanoparticles (White et al, 2015). Future work may focus on modulating the SPION/immune system interaction to more effectively target tumor cells.…”
Section: Box 1 Vision and Challenges Of Thermally Sensitive Nanocarriersmentioning
confidence: 99%
“…(Reichel, Tripathi, & Perez, 2019;Zanganeh et al, 2016). Finally, in preliminary studies, others have also attempted to drive immune cells (microglia) toward regions of interest by functionalizing them with magnetic nanoparticles (White et al, 2015). Future work may focus on modulating the SPION/immune system interaction to more effectively target tumor cells.…”
Section: Box 1 Vision and Challenges Of Thermally Sensitive Nanocarriersmentioning
confidence: 99%
“…Based on this finding, they formulated CNT-cPG therapy and successfully exerted its anti-tumor activity by promoting the influx of inflammatory cells such as macrophages, nature killer cells, CD8 and CD4 cells [109]. Their recent study has even shown that, through the use of iron oxide nanoparticles, they could control the migration of targeted microglia in vitro under an external magnetic field and could further increase the infiltration of inflammatory macrophage to the brain tumor in vivo [110]. …”
Section: 2 Targeting Microglia/macrophages and Tams In The Cnsmentioning
confidence: 99%
“…When the magnetic particle is smaller than the size of an optical mode, the modulation efficiency is reduced. Although single nanoparticles are desirable in some applications, they commonly accumulate in endosomes into aggregates hundreds of nanometers in size [36], which is on the same scale as optical wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent example is magnetic resonance imaging (MRI), which is widely used for full-body human imaging. Coupled with magnetic particles, magnetic fields have also been used for applications such as biomolecule and cell separation [35], cell migration control [36], hyperthermia-based therapy and controlled drug delivery [37], and magnetothermal neural stimulation [38]. Here we use magnetic-field-driven magnetic particles as a new guidestar mechanism.…”
Section: Introductionmentioning
confidence: 99%